2008
DOI: 10.1007/s00018-008-8094-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nef in primate lentiviral immunopathogenesis

Abstract: More than a decade ago it was established that intact nef genes are critical for efficient viral persistence and greatly accelerate disease progression in SIVmac-infected rhesus macaques and in HIV-1-infected humans. Subsequent studies established a striking number of Nef functions that evidently contribute to the maintenance of high viral loads associated with the development of immunodeficiency in the 'evolutionary-recent' human and the experimental macaque hosts. Recent data show that many Nef activities ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
113
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 172 publications
(168 reference statements)
1
113
0
2
Order By: Relevance
“…detection and elimination by the host immune system. It has been previously shown that the accessory HIV-1 Nef protein, which is required for effective viral persistence and greatly accelerates progression to AIDS (32), induces CD95L expression on T cells (33). HIV-1 also infects macrophages and DCs.…”
Section: Cd95 Triggering In Combination With Cd3/28 Activation Inducementioning
confidence: 99%
“…detection and elimination by the host immune system. It has been previously shown that the accessory HIV-1 Nef protein, which is required for effective viral persistence and greatly accelerates progression to AIDS (32), induces CD95L expression on T cells (33). HIV-1 also infects macrophages and DCs.…”
Section: Cd95 Triggering In Combination With Cd3/28 Activation Inducementioning
confidence: 99%
“…16 Delineating the mechanisms of Nef action has been hampered by the multitude of interactions with host T-cell proteins suggested to modulate various intracellular transport and signaling pathways. 17,18 This includes modulating exposure of cell-surface receptors such as MHC-I and II, CD4, and chemokine receptors to evade immune recognition and to prevent superinfection of infected cells, respectively (reviewed in Laguette et al 12 ). In addition, Nef affects the basal states of T-cell activation and the responsiveness of T lymphocytes to TCR signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphotropic viruses also modulate the responsiveness of virally infected T cells to stimulation by interacting APCs in a manner that renders them more permissive for viral replication (12)(13)(14). HIV-1 and other primate lentiviruses manipulate the function of the IS and T cell activation mainly by means of the accessory multifunctional Nef protein, which also impairs MHC Ag presentation and enhances viral infectivity and replication (14)(15)(16). Most importantly, Nef is required for efficient viral replication in vivo and greatly accelerates disease progression in HIV-1-infected individuals (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-2 or SIV nef alleles that downmodulate CD3 block the responsiveness of virally infected primary T cells to TCR-mediated activation, whereas those of HIV-1 and its simian precursors fail to suppress T cell activation and programmed cell death (30). Besides host factors, these differences in Nef function may explain why high levels of chronic immune activation, associated with accelerated T cell turnover rates and apoptosis, are a hallmark of pathogenic HIV-1 infection but are absent in natural nonpathogenic SIV infections (15,31).…”
Section: Introductionmentioning
confidence: 99%